2002
DOI: 10.1530/eje.0.1460649
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular analysis of three families with autosomal dominant neurohypophyseal diabetes insipidus associated with a novel and recurrent mutations in the vasopressin-neurophysin II gene

Abstract: Objective: To test further the hypothesis that autosomal dominant neurohypophyseal diabetes insipidus (adFNDI) is caused by heterozygous mutations in the vasopressin -neurophysin II (AVP-NPII ) gene that exert a dominant negative effect by producing a precursor that misfolds, accumulates and eventually destroys the neurosecretory neurons. Methods: Antidiuretic function, magnetic resonance imaging (MRI) of the posterior pituitary and AVP-NPII gene analysis were performed in 10 affected members of three unreport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
(9 reference statements)
2
21
0
Order By: Relevance
“…Maghnie et al (19) reported this finding in one of five children with adFNDI. We have reported on one case of partial empty sella among ten patients with adFNDI from three families (26). Melo et al described a child with adFNDI and a hypoplastic anterior pituitary with normal anterior pituitary function (27).…”
Section: Discussionmentioning
confidence: 89%
“…Maghnie et al (19) reported this finding in one of five children with adFNDI. We have reported on one case of partial empty sella among ten patients with adFNDI from three families (26). Melo et al described a child with adFNDI and a hypoplastic anterior pituitary with normal anterior pituitary function (27).…”
Section: Discussionmentioning
confidence: 89%
“…In our two patients, the signs and symptoms of CDI became evident by the age of 4 years, suggesting that both mutations are completely penetrant and that children with early-onset CDI must be evaluated for AVP mutations even in the absence of this condition among relatives. Although the most frequent form of familial CDI by far is the autosomal dominant condition (3), to our knowledge, de novo dominant mutations of the AVP gene have been reported as recurrent mutations in three families (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that extrapituitary localizations of LCH including the chest or liver may become evident after the onset of CDI [32]. Rarely, de novo mutations of theAVP-NPII gene are responsible for some idiopathic forms of CDI associated with normal PS size [33,34]. …”
Section: Acquired Forms Of CDImentioning
confidence: 99%
“…7, table 2) [1,13,27,40,41,42,56,57]. Dynamic MRI can help identify cases of CDI and normal PS size associated with abnormal blood supply to the posterior pituitary [33,58]. Diagnostic flowcharts for polyuria, polydipsia and CDI are reported in figures 8 and 9.…”
Section: Diagnosis Of Diabetes Insipidusmentioning
confidence: 99%